Distance delivery of a parent-implemented language intervention for young boys with fragile X syndrome. (September 2017) - Bullard, Lauren; McDuffie, Andrea; Abbeduto, Leonard
Background: In addition to significant cognitive delays, boys with fragile X syndrome display phenotypic characteristics that include delays in language, inattention, social anxiety, and escape-maintained challenging behaviors. Despite these challenges, families affected by fragile X syndrome often have limited access to center-based intervention programs. Methods: The present study utilized a multiple baseline design across participants to examine the preliminary effectiveness of a 12-week, parent-implemented spoken language intervention for three 5- to 7-year-old boys with fragile X syndrome. The goal of the intervention was to teach the biological mothers of each boy to use a set of verbally responsive language support strategies while participating in shared book reading activities with her child. All aspects of the intervention, including pre- and post-treatment measures, were delivered into the family's home via distance video teleconferencing. Results: Results from this study provide preliminary support for the efficacy of this parent-implemented language intervention approach by demonstrating generalized improvements in both targeted maternal strategy use and measures of child spoken language. Conclusions: The present study expands upon prior language intervention research utilizing distance delivery of services for families affected by fragile X syndrome. Additionally, the study provides early support for the feasibility of collecting pre- and post-treatment assessments at a distance.